Case Report: The application of novel imaging technologies in lower extremity peripheral artery disease: NIR-II imaging, OCTA, and LSFG - Ning, Yijie; Hu, Jie; Li, Haifeng; Lu, Chuanlong; Zhang, Zeyu; Yan, Sheng; Shi, Peilu; Gao, Tingting; Wang, Heng; Zhang, Ruijing; Dong, Honglin (Frontiers in Cardiovascular Medicine, 2024)
Lower extremity peripheral artery disease (PAD) is a growing global health problem.New ways have been explored to diagnose PAD in recent years. At present, most of imaging methods for PAD focus on the macrovascular blood flow, and the exploration of microcirculation and tissue perfusion of PAD remains largely insufficient. In this report, we applied three new imaging technologies, second near-infrared region (NIR-II, 900-1,880 nm wavelengths) imaging, optical coherence tomography angiography (OCTA) and laser speckle flowgraphy (LSFG) in a PAD patient with a healthy human subject as control. Our results showed that the PAD patient had poorer tissue perfusion than the control without adverse effects observed. Moreover, compared with the first near-infrared region (NIR-I, 700-900 nm wavelengths) imaging results, NIR-II imaging showed higher signal-to-background ratio (SBR) and resolution than NIR-I imaging, and detected microvessels that were not detected by NIR-I imaging. These observations suggested that NIR-II imaging, OCTA and LSFG were potential safe and effective methods for diagnosing PAD.